Genetic markers of rheumatoid arthritis susceptibility in anti-citrullinated peptide antibody negative patients. Issue 12 (1st June 2012) - Viatte, Sebastien; Plant, Darren; Bowes, John; Lunt, Mark; Eyre, Stephen; Barton, Anne; Worthington, Jane
Abstract : Introduction: There are now over 30 confirmed loci predisposing to rheumatoid arthritis (RA). Studies have been largely undertaken in patients with anticyclic citrullinated peptide (anti-CCP) positive RA, and some genetic associations appear stronger in this subgroup than in anti-CCP negative disease, although few studies have had adequate power to address the question. The authors therefore investigated confirmed RA susceptibility loci in a large cohort of anti-CCP negative RA subjects. Methods: RA patients and controls, with serological and genetic data, were available from UK Caucasian patients (n=4068 anti-CCP positive, 2040 anti-CCP negative RA) and 13, 009 healthy controls. HLA-DRB1 genotypes and 36 single nucleotide polymorphisms were tested for association between controls and anti-CCP positive or negative RA. Results: The shared epitope (SE) showed a strong association with anti-CCP positive and negative RA, although the effect size was significantly lower in the latter (effect size ratio=3.18, p<1.0E-96). A non-intronic marker at TNFAIP3, GIN1/C5orf30, STAT4, ANKRD55/IL6ST, BLK and PTPN22 showed association with RA susceptibility, irrespective of the serological status, the latter three markers remaining significantly associated with anti-CCP negative RA, after correction for multiple testing. No significant association with anti-CCP negative RA was detected for other markers (eg, AFF3, CD28, intronic marker at TNFAIP3), though the study power for those markers was over 80%. Discussion: In the largest sample size studied to date, the authors have shown that the strength of association, the effect size and the number of known RA susceptibility loci associated with disease is different in the two disease serotypes, confirming the hypothesis that they might be two genetically different subsets.